The effectiveness of a floor gully with grating to prevent the oviposition of aedes (Stegomyia) aegypti (Linneaus): a laboratory study - Chen, Chee Dhang; Teoh, Pei Sze; Wan-Norafikah Othman,; Mohd Sofian-Azirun,; Lee, Han Lim (Penerbit UKM, 2009)
This study was conducted to evaluate the effectiveness of a floor gully come with grating to prevent the oviposition of Aedes aegypti in the floor trap. In order to conduct the test, two containers were placed into a mosquito cage (30 cm × 30 cm × 30 cm). Both containers were filled with declorinated seasoned tap water and covered with floor gully c/w grating and normal floor gully, respectively. A total of 50 gravid Ae. aegypti females were then released into the cage and left for a week. All the eggs obtained from the test were allowed to remain inside the containers for the eggs to hatch. The number of hatched larvae was counted and recorded. Five replicates were conducted concurrently. There was a significant difference of Ae. aegypti larvae obtained between container with floor gully c/w grating and normal floor gully (p < 0.05). A total of 96.41% reduction of Ae. aegypti larvae was obtained in the container with floor gully c/w grating compared with the normal floor gully, indicating that the floor gully c/w grating used in this study was able to prevent oviposition of Ae. aegypti in holding water.